THE EFFECTIVENESS OF THE PHARMACY'S ROLE IN PROVIDING DRUG INFORMATION ON TELEPHARMACY - Citta, Warrantia (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2024)
Background: Telepharmacy is a digital technology-based pharmaceutical service that provides telecommunication between patients and related healthcare services. It offers healthcare services such as drug reviews, counseling, and therapeutic communication with patients, as well as online and real-time exchange of prescriptions. Objective: The effectiveness of the pharmacist's role in the delivery of drug information on the use of health apps. Methods: Current descriptive research using purposive sampling technique for data collection from the general public who have used telepharmacy with variable measurement scales in the study referring to the Likert Scale. Results: This study found that 64.8% of respondents had used telepharmacy to obtain medicine or drug information. According to the community, 82.9% stated that the quality of information obtained through telepharmacy was as good as information provided face-to-face by pharmacists. The community also considered that the role of pharmacists in the utilization of telepharmacy is very important and it is hoped that pharmacists can play an active role in providing drug information regularly in the form of leaflets or website links. Conclusion: Telepharmacy is an alternative health service that allows patients to get quick access and convenience in obtaining health services.